Shaping the glioma immune microenvironment through tryptophan metabolism - Platten, Michael; Weller, Michael; Wick, Wolfgang (CNS Oncology, 2012)
SUMMARY The metabolism of the essential amino acid tryptophan is a key microenvironmental factor shaping the immunobiology of many tumor types. The current concept suggests that in the tumor microenvironment, tryptophan is metabolized by specialized dioxygenases, chiefly indoleamine-2,3-dioxygenase (IDO), which is expressed by tumor cells and antigen-presenting cells. High IDO activity leads to the depletion of tryptophan from the local microenvironment, while immediate tryptophan metabolites, particularly kynurenine, accumulate to high micromolar levels. Both the depletion of tryptophan and the accumulation of kynurenine lead to profound suppression of T-cell responses. Orally active IDO inhibitors are currently being explored in clinical trials for their efficacy in enhancing antitumor immune responses. Recent evidence points at alternative routes of tryptophan catabolism via tryptophan-2,3-dioxygenase, which is particularly expressed in malignant gliomas resulting in the production of high amounts of kynurenine. Tryptophan-2,3-dioxygenase-derived kynurenine in turn leads to the promotion of glioma growth and invasiveness and the suppression of antitumor immune responses by binding to the aryl hydrocarbon receptor expressed in glioma cells and glioma-infiltrating T cells. These new data open up novel therapeutic approaches to alleviate glioma-mediated immunosuppression. This review summarizes the current view on the relevance of tryptophan metabolism as an important immunosuppressive, proinvasive and growth-promoting metabolic pathway in malignant glioma.
Gesehen am 03.05.2018